Implementasi Metode Bernyanyi untuk Meningkatkan Hasil Belajar Siswa di Madrasah - Nasri, Nasri (MASALIQ, 2023)
The method comes from the Greek word methodos which comes from the word "meta" means through and "hodos" means way. So the method is the way to go, how to do something or procedure. An effective method is a method that is able to achieve learning goals more quickly and precisely by taking into account the characteristics of the student's subjects, singing is one of the methods that children like most in learning because it tends to be active, lively, cheerful and happy. Learning outcomes can be explained by understanding the two words that make it up, namely "results" and "learning". The definition of result (product) refers to an acquisition as a result of carrying out an activity or process that results in a functional change in input while learning is an individual's effort to obtain a change in behavior. Learning is a process that is directed towards achieving predetermined goals or competencies. Learning can also be interpreted as a process, meaning that in learning there will be a process of seeing, making, observing, solving problems or problems, listening and practicing. Learning outcomes are the abilities possessed by students after they receive their learning experience. When learning ends, students get learning outcomes. Learning outcomes are the result of the interaction of teaching and learning activities.